Mycobacteria in Water and Loose Deposits of Drinking Water Distribution Systems in Finland - Torvinen, Eila (American Society for Microbiology (ASM), 2004)
Drinking water distribution systems were analyzed for viable counts of mycobacteria by sampling water from waterworks and in different parts of the systems. In addition, loose deposits collected during mechanical cleaning of the main pipelines were similarly analyzed. The study covered 16 systems at eight localities in Finland. In an experimental study, mycobacterial colonization of biofilms on polyvinyl chloride tubes in a system was studied. The isolation frequency of mycobacteria increased from 35% at the waterworks to 80% in the system, and the number of mycobacteria in the positive samples increased from 15 to 140 CFU/liter, respectively. Mycobacteria were isolated from all 11 deposits with an accumulation time of tens of years and from all 4 deposits which had accumulated during a 1-year follow-up time. The numbers of mycobacteria were high in both old and young deposits (medians, 1.8 × 10(5) and 3.9 × 10(5) CFU/g [dry weight], respectively). Both water and deposit samples yielded the highest numbers of mycobacteria in the systems using surface water and applying ozonation as an intermediate treatment or posttreatment. The number and growth of mycobacteria in system waters correlated strongly with the concentration of assimilable organic carbon in the water leaving the waterworks. The densities of mycobacteria in the developing biofilms were highest at the distal sites of the systems. Over 90% of the mycobacteria isolated from water and deposits belonged to Mycobacterium lentiflavum, M. tusciae, M. gordonae, and a previously unclassified group of mycobacteria. Our results indicate that drinking water systems may be a source for recently discovered new mycobacterial species.